Accumulation of Toxic Arsenic by Cherry Radish Tuber (Raphanus sativus var. sativus Pers.) and Its Physiological, Metabolic and Anatomical Stress Responses - Pavlíková, Daniela; Pavlík, Milan; Zemanová, Veronika; Novák, Milan; Doležal, Petr; Dobrev, Petre I; Motyka, Václav; Kraus, Kamil (Plants (Basel, Switzerland), 2023)
In a pot experiment, cherry radish (Raphanus sativus var. sativus Pers. 'Viola') was cultivated under two levels of As soil contamination-20 and 100 mg/kg. The increasing As content in tubers with increasing soil contamination led to changes in free amino acids (AAs) and phytohormone metabolism and antioxidative metabolites. Changes were mainly observed under conditions of high As contamination (As100). The content of indole-3-acetic acid in tubers varied under different levels of As stress, but As100 contamination led to an increase in its bacterial precursor indole-3-acetamide. A decrease in cis-zeatin-9-riboside-5'-monophosphate content and an increase in jasmonic acid content were found in this treatment. The free AA content in tubers was also reduced. The main free AAs were determined to be transport AAs (glutamate-Glu, aspartate, glutamine-Gln, asparagine) with the main portion being Gln. The Glu/Gln ratio-a significant indicator of primary N assimilation in plants-decreased under the As100 treatment condition. A decrease in antioxidative metabolite content-namely that of ascorbic acid and anthocyanins-was observed in this experiment. A decline in anthocyanin content is related to a decrease in aromatic AA content which is crucial for secondary metabolite production. The changes in tubers caused by As contamination were reflected in anatomical changes in the radish tubers and roots.
Keywords: metalloid; stress metabolism; vitamin C; methionine; vegetable